Epilepsy After Brain Injury – Understanding the Link and Managing the Condition - Kałuża, Jessica Adriana; Bochenek, Oliwia; Nowak, Aleksandra; Koper, Mateusz; Konaszczuk, Adrian; Ratyna, Klaudia; Kozyra, Oliwia; Szypuła, Zofia; Paluch, Katarzyna; Skarbek, Małgorzata (Quality in Sport, 2024)
Post-Traumatic Epilepsy (PTE) is a neurological disorder characterized by recurrent seizures that occur as a result of traumatic brain injury (TBI). It represents a significant medical challenge due to its complex pathophysiology, diverse clinical manifestations, and the long latency period between the initial injury and the onset of epilepsy. It typically manifests weeks, months, or even years after the initial trauma, complicating the prognosis and management of head injury patients. The incidence of PTE varies widely, influenced by the severity and nature of the brain trauma, with higher risks associated with penetrating injuries, severe brain contusions, and hemorrhagic lesions. Pathogenetic mechanisms involve a cascade of molecular and cellular events, including neuroinflammation, blood-brain barrier disruption, and neuronal hyperexcitability, which contribute to the formation of epileptic networks. Diagnosis relies on a detailed patient history, neuroimaging, and electroencephalography (EEG) to confirm seizure activity and exclude other causes. It is often delayed and complicates early intervention strategies. Current management primarily focuses on seizure control through antiepileptic drugs (AEDs), but response rates are variable, and many patients suffer from drug-resistant epilepsy. Advances in neuroimaging and biomarker research hold promise for earlier detection and targeted therapies. This review synthesizes recent findings on the epidemiology, pathophysiology, diagnosis, and management of PTE, highlighting the need for a multidisciplinary approach to improve outcomes for individuals affected by this condition.